The Effect of Pretreatment with the Hydroalcoholic Extract of Ginger on the Modulation of Dopamine D2 Receptor Agonist and Antagonist Impacts on Pain Sensitivity in Male Rats - Mohammad Hossein Faraji; Mahnaz Taherianfard * (Lorestan University of Medical Sciences, 2022)
Background and Aim: Zingiber officinale (ginger) extract increased dopamine concentration in various brain areas. Therefore, the present study aimed to investigate how ginger extract can affect the efficiency of D2 receptor agonist (bromocriptine) and antagonist (chlorpromazine) on pain sensitivity in rats. Materials and Methods: Forty-eight adult male rats in standard conditions divided into eight groups, i.e. the control, the ginger sham1, sham2, ginger, bromocriptine 10 or 30 µM + ginger, and chlorpromazine 20 or 40 µM + ginger. The cannulation of the lateral ventricle was conducted unilaterally by the stereotaxic procedure. A pain sensitivity test was carried out in all the groups by formalin test on the 16th day. Results: The results of this study indicated that ginger could remarkablly (P<0.01) reduce pain sensitivity in all stages of the formalin test. As the data revealed, bromocriptine 10 or 30 µg/rat and chlorpromazine 20 or 40 µg/rat significantly (P<0.01) decreased the pain sensitivity in all phases of the formalin test in comparison with the control and sham groups. However, chlorpromazine 20 or 40 µg/rat noticeably (P<0.01) increased the pain sensitivity when compared to ginger and bromocriptine groups. Conclusion: According to the results of the present study, ginger mimics the analgesic effect of bromocriptine. Moreover, ginger has attenuated the hyperalgesic effect of chlorpromazine. It seems that ginger has a synergistic effect with the analgesic effect of the dopamine D2 receptor.